The Influence Of Debt To Equity Ratio (DER) And Net Profit Margin (NPM) To Changes In Earnings In Construction And Building Sub-Sector Companies Listed In Indonesia Stock Exchange 2016-2019 - Kiki Tri Rizky; Fika Aryani (Institut Ilmu Sosial dan Manajemen Stiami, 2020)
This study aims to examine and analyze the influence of Debt To Equity Ratio(DER) and Net Profit Margin (NPM) to changes in Earnings in Construction and Building Sub-Sector Companies listed in Indonesia Stock Exchange 2016-2019. A sample of 40 data were obtained using purposive sampling method. This research used a quantitative approach with associative research type. Data analysis method used is multiple linear regression method.The results show that partially the Debt To Equity Ratio has a statistically significant negative effect to change in Earnings, this is indicated by the results of the t test for the variable DER -15.149> 2.026 and Net Profit Margin. statistically significant effect to changes in Earnings as indicated by the t test for the variable NPM 5,753> 2,026. Simultaneously, Debt to Equity Ratio and Net Profit Margin have a significant effect simultaneously to changes in Earnings, this is indicated by the significance of the F test of 0.000 <0.05